Unique Derived Features in Spermiogenesis and Sperm Morphology Supporting a Close Relationship between the Species of Hollandichthys and Rachoviscus (Characiformes: Characidae) - Quagio-Grassiotto, Irani [UNESP]; Malabarba, Luiz R.; Azevedo, Marco A.; Burns, John R.; Baicere-Silva, Clarianna Martins [UNESP]; Quevedo, Rodrigo (Amer Soc Ichthyologists & Herpetologists, 2012)
Hollandichthys and Rachoviscus are endemic to the Atlantic coastal drainages of Brazil and have been historically hypothesized as related to different genera and even subfamilies of the Characidae. We describe the testis morphology, spermiogenesis, and sperm ultrastructure of species of both genera under light, transmission, and scanning electron microscopy, and provide unique characters that support a close relationship among Hollandichthys and Rachoviscus. The testes have a similar organization with a tripartite structure, showing a spermatogenic-cranial region, a differentiating-intermediate region, and a storage-caudal region that is continuous with the sperm duct. During spermiogenesis, the final spermatic differentiation occurs in the luminal compartment of the differentiating-intermediate region of the testis. This is herein termed as partially cystic, being distinct from that of any other characids previously described. At the beginning of spermiogenesis, the centriolar complex lies in a medial position in relation to the nucleus, the nucleus moves and slightly elongates toward the flagellar axis forming an eccentric nuclear fossa, and then the nucleus turns backward and elongates forward. The species of both Hollandichthys and Rachoviscus share the presence of long, spiraling mitochondria in the midpiece that seem to be unique among characids. Sperm competitiveness seems to be a determinant factor in accelerating the rate of phenotypic changes in nucleus length and sperm shape among inseminating characids. This is exemplified by the differences found in sperm nucleus shape and length between the two sister species of Rachoviscus, as well as between these species and their sister lineage (Hollandichthys). The formation of sperm packages was observed in Rachoviscus graciliceps.